Malignant transformation in a cohort of patients with oral epithelial dysplasia. Issue 9 (November 2021) - Hankinson, P.M.; Mohammed-Ali, R.I.; Smith, A.T.; Khurram, S.A.
Abstract: Oral epithelial dysplasia (OED) is often diagnosed in oral potentially malignant disorders (OPMD) and carries an increased risk of malignant transformation. Currently, the reported risk of malignant transformation for OED varies. Here we present the risk in a cohort of 150 patients with OED at a specialist centre. In this cohort 2.6%, 4.1%, and 29.2% cases of mild, moderate, and severe OED, respectively, progressed to oral squamous cell carcinoma at the dysplastic site, while a small number developed a malignant lesion elsewhere. Moreover, 17 patients experienced an increase in grade of dysplasia and two showed histological resolution of their lesions.